2018
DOI: 10.5812/ijpbs.11671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Empowering Mothers of Premature Infants on Their Stress Coping Strategies

Abstract: Background: Premature infants experience many problems during their stay in the neonatal intensive care unit (NICU). Premature birth creates a sense of loss in family members, especially mothers, and causes tension and stress. Moreover, inefficient coping strategies increase stress, incompatibility, and mental problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…But the findings of this study are in agreement with the results of the previous studies [28,34,48,49] and the reason for this difference could be that the care and education that mothers receive, as well as the massage of the baby's body by the mother, have an impact on the increase of mother-baby attachment. Karbandi et al (2015) in their research reported a low attachment rate after birth [27], which was not consistent with the results of the present study. The reason for this disparity can be due to the type of tool used in their study, which is different from the tool used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…But the findings of this study are in agreement with the results of the previous studies [28,34,48,49] and the reason for this difference could be that the care and education that mothers receive, as well as the massage of the baby's body by the mother, have an impact on the increase of mother-baby attachment. Karbandi et al (2015) in their research reported a low attachment rate after birth [27], which was not consistent with the results of the present study. The reason for this disparity can be due to the type of tool used in their study, which is different from the tool used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Coping can help mothers reduce stress so they can show maternal behavior, namely good caring abilities (Rossman et al, 2017). Using efficient coping will regulate emotions, reduce the adverse effects of stress due to premature birth, and increase the ability to interact with the baby and the physical and mental health of the mother (Karbandi et al, 2018). Understanding the coping mechanisms used by mothers of premature babies is the cornerstone of choosing the best approach for mothers to build effective health worker and patient relationships.…”
Section: Discussionmentioning
confidence: 99%